2016
DOI: 10.1017/s0007114516000015
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns of obese and normal-weight women of reproductive age in urban slum areas in Central Jakarta

Abstract: Developing countries including Indonesia imperatively require an understanding of factors leading to the emerging problem of obesity, especially within low socio-economic groups, whose dietary pattern may contribute to obesity. In this cross-sectional study, we compared the dietary patterns and food consumption of 103 obese and 104 normal-weight women of reproductive age (19-49 years) in urban slum areas in Central Jakarta. A single 24-h food recall was used to assess energy and macronutrient intakes (carbohyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
(45 reference statements)
1
17
0
2
Order By: Relevance
“…The names found for the healthy DP were more healthy DP 7 , vegetable DP 8,14 , fruit, vegetables, and soybean DP 11 , 2nd LEVEL Schooling (years) a p = 0.003* p = 0.000* p = 0.000* p = 0.012* p = 0.000* p = 0.000* 0-3 1.00 1.00 1.00 1.00 1.00 1.00 and healthy DP 10,30 . Risk DP resembled the western DP 10 , less healthy DP 7 , and unhealthy DP 30 . With respect to the Brazilian DP, patterns characterized by the presence of rice and beans, but with a slightly different composition, were denominated Brazilian DP 26 or low cost higher-risk DP 13 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The names found for the healthy DP were more healthy DP 7 , vegetable DP 8,14 , fruit, vegetables, and soybean DP 11 , 2nd LEVEL Schooling (years) a p = 0.003* p = 0.000* p = 0.000* p = 0.012* p = 0.000* p = 0.000* 0-3 1.00 1.00 1.00 1.00 1.00 1.00 and healthy DP 10,30 . Risk DP resembled the western DP 10 , less healthy DP 7 , and unhealthy DP 30 . With respect to the Brazilian DP, patterns characterized by the presence of rice and beans, but with a slightly different composition, were denominated Brazilian DP 26 or low cost higher-risk DP 13 .…”
Section: Discussionmentioning
confidence: 95%
“…Eating habits are among the leading causes of chronic non-communicable diseases (NCDs) and mortality 1,2 , and the dietary pattern (DP) approach has been widely used to assess this relationship, given that it may be more predictive of disease risk than evaluating the intake of individual foods or nutrients 3,4 . More specifically, studies that investigated DPs in women revealed the association of some of these patterns with obesity [5][6][7] , cardiovascular risk 8 , hypertension 9 , risk of fracture 10 , cancer 11 , and mortality 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fatty and fried foods indicated a positive multiplicative effect in obesity risk in women in Table 3 . Obese Indonesian women of reproductive age also had unhealthy dietary patterns characterized by consumption of oils and fats through fried foods and snacks [ 28 , 29 ]. This dietary pattern may contribute to a higher risk of obesity among women.…”
Section: Discussionmentioning
confidence: 99%
“…Those who had a higher intake of refined carbohydrates also had a higher prevalence ratio of obesity; however, the interaction between gender and refined carbohydrates intake showed a negative multiplicative interaction. Some other related studies showed that sweet foods and beverages were significant risk factors for obesity [ 28 , 29 , 30 , 31 , 32 , 33 ]. It was also found in one study that one additional spoonful of sugar consumed every day increased the risk of being overweight and obese by about 14% [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pola makan yang tidak teratur memiliki dampak merugikan pada thermogenesis, kadar lemak, dan profil insulin 9 . Pola makan yang tidak sehat dengan kebiasaan konsumsi makanan berlemak seperti pada gorengan dan camilan lebih banyak ditemui pada populasi wanita di permukiman padat penduduk 10 . camilan yang dikonsumsi memang cenderung lebih sedikit bila dibandingkan dengan jumlah pada menu utama, namun frekuensi camilan yang sering dapat menjadikan jumlah kalori yang dikonsumsi setara dengan saat konsumsi menu utama 20 .…”
Section: Pendahuluanunclassified